2022
DOI: 10.3390/ijms23148004
|View full text |Cite
|
Sign up to set email alerts
|

Patients Recovering from Severe COVID-19 Develop a Polyfunctional Antigen-Specific CD4+ T Cell Response

Abstract: Specific T cells are crucial to control SARS-CoV-2 infection, avoid reinfection and confer protection after vaccination. We have studied patients with severe or moderate COVID-19 pneumonia, compared to patients who recovered from a severe or moderate infection that had occurred about 4 months before the analyses. In all these subjects, we assessed the polyfunctionality of virus-specific CD4+ and CD8+ T cells by quantifying cytokine production after in vitro stimulation with different SARS-CoV-2 peptide pools c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…During natural infection, typically after a couple of weeks, the magnitude of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-specific CD4 + and CD8 + memory T-cell response peaks at the maximum and is of the order of 0.5% and 0.2% of the repertoire, respectively ( 2 ). CD4 + T cells display a memory profile (including a specific subset formed by stem cell memory) and are able to produce high levels of both IL-2 and T helper (Th)1 cytokines ( 3 5 ). CD4 + T-cell response is greater than the CD8 + counterpart ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…During natural infection, typically after a couple of weeks, the magnitude of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-specific CD4 + and CD8 + memory T-cell response peaks at the maximum and is of the order of 0.5% and 0.2% of the repertoire, respectively ( 2 ). CD4 + T cells display a memory profile (including a specific subset formed by stem cell memory) and are able to produce high levels of both IL-2 and T helper (Th)1 cytokines ( 3 5 ). CD4 + T-cell response is greater than the CD8 + counterpart ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…CD4 + T cells play a crucial role in effective cellular immunity, and studies have indicated that the selection of HLA class II-restricted antigen targets recognized by CD4 + T cells is of paramount importance for clinical outcome ( 45 49 ). CD4 + T cells support B-cell responses in the germinal center, and some CD4 + T cells also have direct antiviral properties similar to those of CD8 + T cells ( 48 , 50 52 ). Furthermore, the FluoroSpot results indicated that the B-cell epitope may contain murine CD8 + T-cell epitopes, and the CD8 + T cells were expanded and survived due to the function of effective CD4 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, in a recent study, the percentage of CD4 + and CD8 + T cells simultaneously producing IFN‐γ, tumor necrosis factor (TNF), interleukin (IL)‐2, IL‐17, and granzyme B and expressing CD107a was measured in patients who had recovered from a mild or severe form of COVID‐19, compared to patients with current mild or severe COVID pneumonia. After 4 months, patients who had recovered from a severe form displayed high proportions of antigen‐specific CD4 + T cells that produce IFN‐γ, TNF, and IL‐2 and were characterized by polyfunctional SARS‐CoV‐2‐specific CD4 + T cells (Paolini et al., 2022). Similar results were observed in those who recovered from a mild form of COVID‐19 pneumonia.…”
Section: Introductionmentioning
confidence: 99%